Impact of Nonsurgical Treatment of Asymptomatic Apical Periodontitis on the Oral Health-related Quality of Life: A Prospective Study - do Nascimento, Angela Longo; Weissheimer, Theodoro; Schunke Gomes, Maximiliano; Ricardo Pereira, Jefferson; Abreu da Rosa, Ricardo; Reis SÃ³, Marcus Vinicius (Iranian Endodontic Journal, 2022)
Introduction: The aim of this study was to evaluate the impact of nonsurgical root canal treatment (nRCT) and the healing of asymptomatic apical periodontitis (AAP) on the oral health-related quality of life (OHRQoL) in a Brazilian population. Materials and Methods: This prospective longitudinal observational study included 56 adults, in which 84 teeth with asymptomatic apical periodontitis underwent nonsurgical root canal treatment. Socio-demographic and medical data were collected; the primary outcome oral health-related quality of life was measured by the short form of the Oral Health Impact Profile (OHIP-14). Statistical analysis was carried out by Mann-Whitney U-test, and changes in the oral health-related quality of life scores post-treatment were estimated by Student t-test. Results: The mean age was 51.0±15.2 years, with 53.5% of females. Overall, nRCT significantly improved the OHRQoL (P<0.001, effect size=0.76). Gender (female) was associated with a higher OHRQoL after nRCT (P<0.05). OHIP-14 showed a significant reduction six months after root canal treatment compared to baseline scores. Conclusion: Present findings revealed that nonsurgical root canal treatment improved the oral health-related quality of life in patients with asymptomatic apical periodontitis.